(untitled) (Materiali di Estetica. Terza serie, 2021)
In the 1950s, in an important and innovative period of Milanese architecture, Enzo Paci dedicated about ten essays to architecture, deriving from his friendly relationships a real research on architectural thought. This article shows that he is elaborating a phenomenological and relational conception of the Lebenswelt: in this philosophical perspective, he considers the city as an ideal type in which a harmonious whole of relationships takes shape. The architecture is not mere structure, but the expression of a coexistence in free intentional relationships immersed in concrete life.